Schwann cells: Rescuers of central demyelination - Garcia Diaz, Beatriz; Baron Van Evercooren, Anne (Wiley, 2020)
The presence of peripheral myelinating cells in the central nervous system (CNS) hasgained the neurobiologist attention over the years. Despite the confirmed presence ofSchwann cells in the CNS in pathological conditions, and the long list of their beneficialeffects on central remyelination, the cues that impede or allow Schwann cells to success-fully conquer and remyelinate central axons remain partially undiscovered. A betterknowledge of these factors stands out as crucial to foresee a rational therapeuticapproach for the use of Schwann cells in CNS repair. Here, we review the diverse originsof Schwann cells into the CNS, both peripheral and central, as well as the CNS compo-nents that inhibit Schwann survival and migration into the central parenchyma. Namely,we analyze the astrocyte- and the myelin-derived components that restrict Schwanncells into the CNS. Finally, we highlight the unveiled mode of invasion of these peripheralcells through the central environment, using blood vessels as scaffolds to pave their waystoward demyelinated lesions. In short, this review presents the so far uncovered knowl-edge of this complex CNS-peripheral nervous system (PNS) relationship
Keywords: Sistema nervioso central; Blood vessels; Central Nervous System; Myelin; Schwann cells; Astrocytes; Remyelination